Evaluation of Allplex™ Entero-DR assay for detection of antimicrobial resistance determinants from bacterial cultures (2020)
Objective To evaluate the sensitivity and specificity of the Allplex™ Entero-DR, a quantitative PCR-based method, for the detection of β-lactamase-encoding genes and vancomycin-resistance determinants in 156 previously characterized Gram-negative bacilli and Enterococcus spp. from bacterial cultures. Result The method had 100% sensitivity and between 92 and 100% of specificity for identifying blaKPC, blaVIM, blaIMP, blaNDM, blaOXA-48-like, blaCTX-M and vanA. In nine isolates, unspecific amplifications were detected. The Ct of these false positives was above 33. The Ct of the correctly identified bla and van genes did not surpass 28 and 30, respectively. None of the clinical isolates included as negative controls yielded any amplification. Therefore, the Allplex™ Entero-DR assay is a highly accurate test for the detection of important antibiotic resistance determinants. With this assay, reliable results can be obtained within 3 h. However, according to our data, samples with Ct values greater than 33 should be considered with caution.